Selected aspects of due diligence of sovereigns - Hyżyk, Sebastian (Copernican Journal of Finance & Accounting, 2013)
The purpose of this paper is to present and analyse the prevailing credit rating methodologies, as an element of due diligence process of countries, in the light of the attributes of the sovereigns and associated risks. The concept of sovereignty introduces many variables to the due diligence analysis and in particular to credit risk analysis. The multidimensional character of a sovereign and its complex decision-making process require special attention from the creditors. The prevailing methodologies stress the fact that both quantitative and qualitative elements need to be taken into consideration. Debt affordability, referring to debt size and financial ability to repay it, remains an important factor in a quantitative analysis, but not a decisive one. Qualitative elements such as the assessment of the institutional capacity become essential, since in the case of the sovereigns, the ability to repay does not necessarily imply the willingness to repay. Due diligence of IFIs goes beyond traditional credit risk assessment in the domains, where states ‘surrender’ their sovereignty to the regulation of international law, particularly in the sphere of human rights and environment.